Latin American and Caribbean trade and investment relations with the United States in the 1980s (IDB WashingtonUS, 1991)
Looks at trade policy in Latin America in the 1980s. Examines United States merchandise trade with Latin America and the Caribbean and reviews United States direct investment in Latin America and the Caribbean 1980-1989.
DC